KOLABORASI PEMERINTAH DAN LSM DALAM PEMBERDAYAAN NELAYAN UNTUK KESEJAHTERAAN MASYARAKAT PESISIR - Henri; Nasir (STISIP Widyapuri Mandiri, 2025)
Fishing communities in Pangkajene and Islands Regency (Pangkep) face various structural challenges such as limited capital, low access to technology, and dependence on daily catches which have an impact on low levels of welfare. To overcome these problems, collaborative efforts are made between local governments and Non-Governmental Organizations (NGOs) in the implementation of coastal community empowerment programs. This research aims to examine the forms of collaboration between the government and NGOs and assess their contribution to empowering and improving the welfare of the fishing community. The approach used is descriptive qualitative with data collection techniques in the form of in-depth interviews, observations, and documentation of informants from the government, NGOs, and fishermen's groups. The findings show that the collaboration has resulted in programs such as training, economic assistance, and environmental education that have a positive impact on community capacity building. However, collaboration still faces obstacles in coordination, program sustainability, and uneven community participation. This research contributes to enriching the literature on collaborative governance in the context of empowering coastal communities, as well as a reference for governments and NGOs to design collaboration strategies that are more inclusive, sustainable, and based on local needs.